Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 327 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Coccothrinax argentea (Lodd. ex Schult. & Schult.f.) Sarg. ex Becc." ] } The dataset includes 327 records from 30 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0004112-150922153815467/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences